2012
DOI: 10.1038/aps.2012.68
|View full text |Cite
|
Sign up to set email alerts
|

Dose findings of antofloxacin hydrochloride for treating bacterial infections in an early clinical trial using PK-PD parameters in healthy volunteers

Abstract: Aim: To find an appropriate dose regimen of the novel antibacterial agent antofloxacin for a phase II clinical trial using a population pharmacokinetic (PPK) study in healthy volunteers and the minimum inhibitory concentration (MIC) as pharmacodynamic (PD) parameters. Methods: Twenty-four healthy volunteers were enrolled in a double-blind crossover study and received antofloxacin (200 or 400 mg/d, po) for consecutive 5 d with 10 d washout between two separate periods. Blood concentrations were analyzed using H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This microbiological response in the animal model was analogous to, or in excess of, that of the currently available "respiratory" fluoroquinolones levofloxacin and moxifloxacin, which required an AUC 0 -24 /MIC ratio of Ͼ100 to produce a significant bactericidal effect (12). Once more, an early clinical trial showed that antofloxacin had clinical and bacteriological outcomes for K. pneumoniae (30 strains) and E. coli (33 strains) similar to those of levofloxacin (13). In general, fluoroquinolones have good penetration into ELF, and our study confirms this observation (14,15).…”
Section: Discussionmentioning
confidence: 82%
“…This microbiological response in the animal model was analogous to, or in excess of, that of the currently available "respiratory" fluoroquinolones levofloxacin and moxifloxacin, which required an AUC 0 -24 /MIC ratio of Ͼ100 to produce a significant bactericidal effect (12). Once more, an early clinical trial showed that antofloxacin had clinical and bacteriological outcomes for K. pneumoniae (30 strains) and E. coli (33 strains) similar to those of levofloxacin (13). In general, fluoroquinolones have good penetration into ELF, and our study confirms this observation (14,15).…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies showed that the protein binding rate of chinfloxacin was 17.5%, the MIC 90 range was 0.03 to 1 mg/liter for most clinical isolates, and the AUC ss was around 51.53 mg·h·liter Ϫ1 after multiple oral administrations of 400 mg. The AUC ss value from the 400-mg multiple-dose PK study could make the fAUC ss /MIC of chinfloxacin higher than the PK/PD breakpoints of fluoroquinolones related to clinical efficacy and thereby meet the therapeutic target value of fluoroquinolones for clinical use (19)(20)(21). This suggests that 400 mg of chinfloxacin is an appropriate dose for future clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, high‐performance liquid chromatography (HPLC) has been the most commonly used method in analyzing antofloxacin and its derivatives (Xiao et al, ; Li et al, ). In most of the previous work, the parent drug was the only parameter that has been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the previous work, the parent drug was the only parameter that has been analyzed. Nevertheless, the cumulative urinary elimination percentage of antofloxacin after the last dose within 96 h was no more than 56% (Xiao et al, ; Li et al, ). It was a time‐consuming method with undesired results; new method needs to be established to shorten the analysis time and raise the sensitivity and accuracy.…”
Section: Introductionmentioning
confidence: 99%